The Effectiveness of Perceived Enjoyment and Brand Engagement in Correlating Gamification Marketing with Online Repurchase Intention in Shopee Game Users - Mila Almaudina; Asep Muhammad Ramdan; Dicky Jhoansyah; Mazzlida Mat Deli (International Journal of Economics Development Research (IJEDR), 2023)
This study was conducted with the aim of knowing how much influence and effectiveness of perceived enjoyment and brand engagement in mediating the relationship between gamification marketing on online repurchase intention in shopee games users. The research method used in this research is descriptive causal method with a quantitative approach. This research was conducted by distributing questionnaires online to 250 respondents. The data analysis technique in this study is the Structural Equational Modeling (SEM) technique using IBM SPSS AMOS 24 software. The results of this study indicate that the role of perceived enjoyment and brand engagement has a positive and significant effect and is effectively used in the gamification marketing relationship to increase online repeat purchase intention for shopee games users.